A Potential Application of a Piezoelectric Atomiser for Ophthalmic Drug Delivery - Wei Xia; Hung-Yao Hsu; Lingxue Kong; Allan Evans; Ryan Lee (Applied Bionics and Biomechanics)
A liquid atomiser composed of a piezoelectric transducer and a metal plate with numerous micro-apertures is studied to identify the most influential factors on its atomising performance. The Taguchi method is employed in the experiment design and analysis of the study on how each factor acts in the atomising process. An optimal condition is determined for producing a stream of droplets. The study shows that the droplet size and the spraying velocity are suitable for ophthalmic drug delivery application, with an even distribution of the drug over most of the eyeball surface area due to the controllable cross-sectional area of the droplet stream. This greatly improves the treatment effectiveness and efficiency of eye therapy. Finally, a structure of the ophthalmic drug delivery system is proposed.